Peran Usaha Mikro Kecil Menengah (UMKM) dalam Pemberdayaan Ekonomi Masyarakat Desa - Raju Gobal; Yohanis Tasik Allo; Duryana (CV. Creative Tugu Pena, 2024)
This study aims to explore the role of Micro, Small, and Medium Enterprises (MSMEs) in empowering the community's economy, especially in rural areas. MSMEs are known as the main drivers of the local economy that make significant contributions to creating jobs, increasing household income, and reducing poverty. This study uses a qualitative literature approach by collecting and analyzing data from various literature sources, including books, journal articles, research reports, and relevant government documents. The results of the study indicate that MSMEs have a strategic role in diversifying the local economy, increasing competitiveness, and empowering communities through improving human resource skills and capacity. However, MSMEs also face various challenges, such as limited access to capital and financing, lack of training and mentoring, and limited market access. Therefore, greater support is needed from the government, financial institutions, and the private sector to overcome these obstacles and optimize the role of MSMEs in sustainable economic development. This study is expected to provide insights and recommendations for policy makers and MSME actors in increasing the contribution of MSMEs to community economic empowerment.